Development of geopolymeric mortars produced from industrial wastes in both precursor and activator phases - Mendes, Beatryz Cardoso (2022)
Geopolymers are binder materials that can be an alternative to replace Portland cement. They are considered less aggressive to the environment because of the lower emission of CO 2 and use of energy in their production chain. However, in order to obtain this advantage, it is essential to use activators that were produced cleanly and sustainably, which is not the case of commercial products such as sodium silicate. This work aimed to manufacture a more eco- efficient product using industrial wastes. Geopolymeric pastes and mortars were produced from chamotte as precursor and waste glass as a component of an alternative activator. In the first experimental phase, it was evaluated the effect of molar concentration and waste glass content in the alkaline solutions. A factorial design of experiments with two factors – molar concentration and waste glass content – and three and four levels, respectively, was applied to analyze the effects. Physical and mechanical tests were performed, as well as the microstructural analyses. The environmental impacts of replacing the traditional activator by the WG-based one were also assessed. The best solutions were selected to develop the mortars, keeping chamotte as precursor and using river sand as fine aggregate. These mortars were produced and characterized for physical and mechanical properties. The results obtained showed that the WG content strongly affects the mechanical strength of geopolymers and the quality of the matrices, promoting a greater formation of geopolymerization products. Using an alternative alkaline solution can reduce 69.8% of the embodied energy and 78.0% of CO 2 footprint compared to the traditional waterglass-based activators. Therefore, this research contributes to technical literature on the application of industrial wastes in geopolymer and the understanding of geopolymerization process. Keywords: Geopolymer. Waste glass. Chamotte. Sustainability.